Aktivitas Antibakteri Sediaan Sabun Cair Ekstrak Daun Waru (Hibiscus tiliaceus L) Terhadap Staphylococcus aureus - Irawanda, Rahma; Umar, Anugrah; Astari, Chitra (Jurnal Mandala Pharmacon Indonesia, 2024)
Skin infectious diseases in humans are a very frequent type of disease, in the human population there are about 30% colonized by Staphylococcus aureus. The skin is the main defense against bacteria if the skin is no longer protected, it will be very easily infected with bacteria, fungi, viruses, protozoa and many other small groups such as Rickettsia, Mycoplasma and Chlamydia.waru plants (Hibiscus tiliaceus L) contain saponins, flavanoids, polyphenols and triterpenoid compounds. The purpose of the study was to determine the physical quality of the waru leaf extract liquid soap formula and to determine which waru leaf extract liquid soap formula has the best inhibition zone against Staphylococcus aureus bacteria. This type of research is an experimental method. The physical quality test of liquid soap showed that the liquid soap was stable. Testing antibacterial activity using the disc diffusion method, the results obtained by the clear zone in F1 show an average value of 25.75, F2 shows an average value of 19.4, and in F3 shows 30.4. From this study, good results were obtained on the physical quality of waru leaf extract liquid soap preparations in all formulas. Of the three best formulas, F3 and provides the greatest antibacterial effect with an average inhibition zone of 30.4 with a very strong category. Keywords : Antibacterial, Waru leaf, Liquid soap, Staphylococcus aureus